An Examination on Edip Yuksel's Interpretation of Q. 4:34 - Sitanggang, Nadya Utari Boru (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2017)
Q.4:34 is frequently used to justify men’s domination over women. There are some keywords in this verse that Edip Yuksel thought have been mistranslated and misunderstood by many scholars, then he reinterpreted them. The authors employed five principles to establish their work, “Quran: A Reformist Translation”. Those five principles are what shaped the work and what influenced the final result of the interpretation. This article uses their principles as tool to criticize the interpretation, so it is called internal criticism. Finally, this work concludes that Edip Yuksel’s interpretation valuated by the five principles is relatively implemented well, the lack is located in the author’s attitude to decide the meaning rashly without explaining the reason they finally chose the meaning after criticizing other’s work. Keywords: 4:34, mistranslated, misunderstood, internal criticism.